Time-resolved co-transport dynamics of microplastics and antibiotic resistance genes during stormwater first flush - Taehwan Lee; Hongmok Jo; Min-Sang Kim; Yeongmi Park; Uijeong Han; Jaehun Gwon; Seon-Young Kim; Seunghyun Lee; Ran Kim; Hyoyoung Lee; Gopalakrishnan Kumar; Si-Kyung Cho (Environmental Research, 2026)

Multicolor vanadium dioxide-polyvinylpyrrolidone/silver bilayer smart films for reconfigurable visible color and solar energy modulation - Yoonjoo Choi; Byoungsu Ko; Hyungyoon Choi; Giyong Park; Sunga Kim; Ho Young Woo; Da Won Lee; Ran An; Yerin Kim; Sung-Hoon Hong; Junsuk Rho; Tianshuo Zhao; et al. (Chemical Engineering Journal, 2026)

A Novel Strain Bifidobacterium longum subsp. longum HN001 Ameliorates High-Fat Diet-Induced Obesity in Mice Through Microbiome-Associated Short-Chain Fatty Acids - Chae Hwan Lee; Youngji Han; Joo Young Ryu; Minseo Jung; Chae Rin Park; Mi Ran Jang; Youn Gil Kwak; Hanvit Cha; Jin Hyup Lee (Probiotics and Antimicrobial Proteins, 2026)

Integrated hydroprocessing and microbial biotransformation of coconut oil to α,ω-diacids - Bashu Dev Pardhe; Il-Ho Choi; Chang Hoon Lee; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Hwabong Jeong; Jongbeom Park; Kyung Taek Heo; et al. (Bioresource Technology, 2025)

Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Crystallization-driven effect enables organic solar cells with efficiency exceeding 19.4 % - Tengfei Han; Jie Chi; Ran Dong; ShuLin Han; Hang Zhou; Yujie Xu; Byung Hui Lee; Lei Cai; Xiaoyan Du; Han Young Woo; Fujun Zhang; Chao Zhang; et al. (Chemical Engineering Journal, 2025)

Identification and functional analysis of MYB group transcripts in formation and development of rose prickle - Ka Youn Lee; Yae Jin Kim; Chang Ho Ahn; Kyoung Ran Do; Youn Jung Choi; Jae A. Jung; O Hyeon Kwon; Hye Ryun An; So Hyeon Lim; Su Young Lee (Euphytica, 2025)

Impact of thawing methods and packaging sizes on the physicochemical and microbial quality of frozen kimchi - Hee Eun Kim; Yun-Jeong Choi; Dong Hyun Park; Min Jung Lee; Minji Kim; Sung Jin Park; Ji Young Choi; Mi Ran Kang; Sung Hee Park; Mi-Ai Lee (International Journal of Refrigeration, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Association between TGF-β/BMP signaling pathway polymorphisms and the risk of primary ovarian insufficiency in Korean women - Yong Hyun Ha; Ji Hyang Kim; Chang Soo Ryu; Ji Won Kim; Eun Ju Ko; Jeong Yong Lee; Ji Eun Shin; Young Ran Kim; Eun Hee Ahn; Nam Keun Kim (Genes & Genomics, 2024)

Safety of applying influenza-antigen-coated microneedles to rat skin and the antigen specific immune response in vivo - Taek-Seon Yun; Bomin Song; Yu-Rim Hwang; Minki Jin; Hyeseung Seonwoo; Donki Kim; Hye Won Kim; Byeong Cheol Kim; Daekyung Kim; Boyeong Park; Jeong Yeon Kang; Seung-Ki Baek; et al. (Journal of Pharmaceutical Investigation, 2024)

Hydroprocessing characteristics of palm fatty acid distillate in palm oil into low-carbon biofuel - Soo Hyun Kim; Hyerim Ko; Mi Ran Lee; Jin-Kuk Kim; Young-Woong Suh (Fuel, 2024)

Molecular mapping of the broad bean wilt virus 2 resistance locus bwvr in Capsicum annuum using BSR-seq - Jung-Min Kim; Joung-Ho Lee; Se-Ran Park; Jin-Kyoung Kwon; Na-Young Ro; Byoung-Cheorl Kang (Theoretical and Applied Genetics, 2024)
Key message Bulked segregant RNA seq of pools of pepper accessions that are susceptible or resistant to Broad bean wilt virus 2 identifies a gene that might confer resistance to this devastating pathogen. Abstract The single-stranded positive-sense RNA virus Broad bean wilt virus 2 (BBWV2) causes substantial damage to pepper ( Capsicum annuum ) cultivation. Here, we describe mapping the BBWV2 resistance locus bwvr using a F 7:8 recombinant inbred line (RIL) population constructed by crossing the BBWV2-resistant pepper accession ‘SNU-C’ with the susceptible pepper accession ‘ECW30R.’ All F 1 plants infected with the BBWV2 strain PAP1 were susceptible to the virus, and the RIL population showed a 1:1 ratio of resistance to susceptibility, indicating that this trait is controlled by a single recessive gene. To map bwvr , we performed bulked segregant RNA-seq (BSR-seq). We sequenced pools of resistant and susceptible lines from the RILs and aligned the reads to the high-quality ‘Dempsey’ reference genome to identify variants between the pools. This analysis identified 519,887 variants and selected the region from 245.9–250.8 Mb of the Dempsey reference genome as the quantitative trait locus region for bwvr . To finely map bwvr , we used newly designed high-resolution melting (HRM) and Kompetitive allele specific PCR (KASP) markers based on variants obtained from the BSR-seq reads and the PepperSNP16K array. Comparative analysis identified 11 SNU-C-specific SNPs within the bwvr locus. Using markers derived from these variants, we mapped the candidate bwvr locus to the region from 246.833–246.949 kb. SNU-C-specific variants clustered near DEM.v1.00035533 within the bwvr locus. DEM.v1.00035533 encodes the nitrate transporter NPF1.2 and contains a SNP within its 5′ untranslated region. The bwvr locus, which contains four genes including DEM.v1.00035533, could represent a valuable resource for global pepper breeding programs.

Establishment of an Agrobacterium-mediated genetic transformation and CRISPR/Cas9-mediated mutagenesis of haploid inducer genes in Pak-choi plants (Brassica rapa ssp. chinensis) - Young-Cheon Kim; May Phyo Thu; Falguni Maliha Rahman; Young Jae Yun; Jin Hoon Jang; Ok Ran Lee; Jeong Hwan Lee (Plant Biotechnology Reports, 2024)

Diuron-induced fetal Leydig cell dysfunction in in vitro organ cultured fetal testes - Ran Lee; Won-Young Lee; Hyun-Jung Park (Reproductive Toxicology, 2024)

Relationship between PM1.0 and PM2.5 in urban and background areas of Republic of Korea - Sujin Kwon; Soo Ran Won; Hyung Bae Lim; Sung Chul Hong; Yong Mi Lee; Ji Yun Jung; Sung-Deuk Choi; Sang-Jin Lee; Seungmee Oh; Ju Young Kim; Yong Pyo Kim; Hye Jung Shin; et al. (Atmospheric Pollution Research, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Establishment of a qualified ex vitro-acclimatized whole plant reproduction system using secondary somatic embryos in Panax ginseng - Ju Hee Kim; Mi Young Kim; Jae Hyun Lee; Jang Uk Kim; Ok Ran Lee (Plant Biotechnology Reports, 2023)

Nanoscale level gelatin-based scaffolds enhance colony formation of porcine testicular germ cells - Ran Lee; Hyun Jung Park; Won Young Lee; Youngsok Choi; Hyuk Song (Theriogenology, 2023)

Multiple low-dose radiation-induced neuronal cysteine transporter expression and oxidative stress are rescued by N-acetylcysteine in neuronal SH-SY5Y cells - Ji-Young Yoo; Ye-Ji Lee; Yu-Jin Kim; Tai-Kyoung Baik; Jun-Ho Lee; Mi‑Jo Lee; Ran-Sook Woo (NeuroToxicology, 2023)

Correction to: A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2022)

Radiological Investigation of Gas Embolism in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) - Adams Hei Long Yuen; Sang Wha Kim; Sung Bin Lee; Seyoung Lee; Young Ran Lee; Sun Min Kim; Cherry Tsz Ching Poon; Jun Kwon; Won Joon Jung; Sib Sankar Giri; Sang Guen Kim; Jeong Woo Kang; et al. (Frontiers in Marine Science, 2022)
Cetaceans have long been considered biologically adapted to suffer no adverse effects from diving-related tissue gas tension. However, increasing reports of gas embolism in cetaceans inhabiting European, Mediterranean and American waters have challenged the conventional understanding of marine mammal diving physiology. In human hyperbaric medicine, virtopsy techniques such as post-mortem computed tomography (PMCT) facilitate the visualization of gas embolism and could be performed adjunct to conventional autopsy. This research presents the first case of gas embolism identified in an East Asian finless porpoise inhabiting Asian waters. Massive gas embolic lesions were found in the liver, which had been compressing both the lungs and abdominal organs, and signs of pneumonia and parasitic infection were observed in both lungs. It is hypothesized that this porpoise might have been unable to expel in vivo gas bubbles from its circulation due to pulmonary dysfunction. Consequently, gas bubbles agglomerated in the liver, resulting in the development of gas embolic lesions. The findings of the present study provide insights into the occurrence of gas embolism in the East Asian finless porpoise, highlighting the potential of PMCT as a promising tool for the diagnosis of gas embolism in stranded cetaceans.

A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2021)

Clinical factors influencing the performance of bacterial multiplex polymerase chain reaction in patients with community-onset pneumonia - Ga Eun Park; Kyong Ran Peck; Jae-Hoon Ko; Cheol-In Kang; Sun Young Cho; Doo Ryeon Chung; Nam Yong Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Hepatocyte CREBH deficiency aggravates inflammatory liver injury following chemokine-dependent neutrophil infiltration through upregulation of NF-κB p65 in mice - Jung-Ran Noh; Jae-Hoon Kim; Soon-Young Na; In Bok Lee; Yun Jeong Seo; Jung Hyeon Choi; Youngwon Seo; Tae Geol Lee; Hueng-Sik Choi; Yong-Hoon Kim; Chul-Ho Lee (Archives of Toxicology, 2020)

Clinical effectiveness of oral antimicrobial therapy for acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Kyoung Ree Lim; Hyunju Lee; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Evaluating the optimal dose of teicoplanin with therapeutic drug monitoring: not too high for adverse event, not too low for treatment efficacy - Si-Ho Kim; Cheol-In Kang; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Soo-Youn Lee; Yae-Jean Kim; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Eravacycline, a newly approved fluorocycline - Young Ran Lee; Caitlin Elizabeth Burton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Neuregulin1 Attenuates H2O2-Induced Reductions in EAAC1 Protein Levels and Reduces H2O2-Induced Oxidative Stress - Jun-Ho Lee; Ji-Young Yoo; Han-byeol Kim; Hong-Il Yoo; Dae-Yong Song; Sun Seek Min; Tai-Kyoung Baik; Ran-Sook Woo (Neurotoxicity Research, 2019)

Metformin Inhibits the Development of l-DOPA-Induced Dyskinesia in a Murine Model of Parkinson’s Disease - Young-Kyoung Ryu; Hye-Yeon Park; Jun Go; Dong-Hee Choi; Yong-Hoon Kim; Jung Hwan Hwang; Jung-Ran Noh; Tae Geol Lee; Chul-Ho Lee; Kyoung-Shim Kim (Molecular Neurobiology, 2018)

Toxicity of Juniperus oxycedrus oil constituents and related compounds and the efficacy of oil spray formulations to Dermatophagoides farinae (Acari: Pyroglyphidae) - Jun-Ran Kim; Haribalan Perumalsamy; He Min Shin; Sang-Guei Lee; Young-Joon Ahn (Experimental and Applied Acarology, 2017)

6-Hydroxydopamine induces nuclear translocation of apoptosis inducing factor in nigral dopaminergic neurons in rat - Hong-Il Yoo; Gil-Yeong Ahn; Eun-Jin Lee; Eu-gene Kim; Sung-Young Hong; Sang-Jin Park; Ran-Sook Woo; Tai-Kyoung Baik; Dae-Yong Song (Molecular & Cellular Toxicology, 2017)

Complete mitochondrial genome of the beluga whale Delphinapterus leucas (Cetacea: Monodontidae) - Ji Hyung Kim; Young-Ran Lee; Jeong-Rack Koh; Jin Woo Jun; Sib Sankar Giri; Hyoun Joong Kim; Cheng Chi; Saekil Yun; Sang Geun Kim; Sang Wha Kim; Hye Kwon Kim; Dae Gwin Jeong; et al. (Conservation Genetics Resources, 2017)

Terpenes from Forests and Human Health - Kyoung Sang Cho; Young-ran Lim; Kyungho Lee; Jaeseok Lee; Jang Ho Lee; Im-Soon Lee (Toxicological Research, 2017)

Neuroanatomical distribution of galectin-3 in the adult rat brain - Hong-Il Yoo; Eu-Gene Kim; Eun-Jin Lee; Sung-Young Hong; Chi-Sun Yoon; Min-Ju Hong; Sang-Jin Park; Ran-Sook Woo; Tai-Kyoung Baik; Dae-Yong Song (Journal of Molecular Histology, 2017)

Alternative new mesenchymal stem cell source exerts tumor tropism through ALCAM and N-cadherin via regulation of microRNA-192 and -218 - Ran Kim; Sang In Park; Chang Youn Lee; Jihyun Lee; Pilseog Kim; Sekyung Oh; Hojin Lee; Min Young Lee; Jongmin Kim; Yong-An Chung; Ki-Chul Hwang; Lee-So Maeng; et al. (Molecular and Cellular Biochemistry, 2017)

Acaricidal activity of Asarum heterotropoides root-derived compounds and hydrodistillate constitutes toward Dermanyssus gallinae (Mesostigmata: Dermanyssidae) - Jun-Ran Kim; Haribalan Perumalsamy; Ju-Hee Lee; Young-Joon Ahn; Young Su Lee; Sang-Guie Lee (Experimental and Applied Acarology, 2016)

Fermented Saccharina japonica (Phaeophyta) improves neuritogenic activity and TMT-induced cognitive deficits in rats - Hyun-Jung Park; Mi-Sook Lee; Hyun Soo Shim; Gyeong-Ran Lee; Sun Yong Chung; Young Mi Kang; Bae-Jin Lee; Yong Bae Seo; Kyung Soo Kim; Insop Shim (Algae, 2016)

Ethnobotany of the wild edible plants gathered in Ulleung Island, South Korea - Homervergel G. Ong; Jae-Min Chung; Hye-Ran Jeong; Young-Dong Kim; Kyung Choi; Chang-Ho Shin; You-Mi Lee (Genetic Resources and Crop Evolution, 2016)

Transcriptomic study of mouse embryonic neural stem cell differentiation under ethanol treatment - Chanchal Mandal; Ji Hyun Park; Mi Ran Choi; Sun Hwa Kim; Abimbola Comfort Badejo; Jin Choul Chai; Young Seek Lee; Kyoung Hwa Jung; Young Gyu Chai (Molecular Biology Reports, 2015)

Global Transcriptome Profiling of Genes that Are Differentially Regulated During Differentiation of Mouse Embryonic Neural Stem Cells into Astrocytes - Dalmuri Han; Mi Ran Choi; Kyoung Hwa Jung; Namshin Kim; Se kye Kim; Jin Choul Chai; Young Seek Lee; Young Gyu Chai (Journal of Molecular Neuroscience, 2015)

Polymorphisms of interleukin-31 are associated with anti-CCP levels in females with rheumatoid arthritis - JI-IN YU; YOUNG-RAN PARK; SHIN-SEOK LEE; SOO-CHEON CHAE (Journal of Genetics, 2014)

Role of vacuolating cytotoxin VacA and cytotoxin-associated antigen CagA of Helicobacter pylori in the progression of gastric cancer - Mi-Ran Ki; Meeyul Hwang; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Myeong-Mi Lee; Soo-Eun Sung; Sang-Hyeob Kim; Hye Seung Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2014)

Toxicity assessment of a novel silk fibroin and poly-methyl-methacrylate composite material - Min Ju Chae; Dae Won Kim; Yun Joong Kim; Hae Yong Kweon; Yong-Jun Cho; Soo Young Choi; Hae Ran Lee (Molecular & Cellular Toxicology, 2014)

ENA-A actimineral resource A extends lifespan associated with antioxidant mechanism in SMP30 knockout mice - Jung-Youn Han; Meeyul Hwang; Sung-Yong Hwa; Jin-Kyu Park; Mi-Ran Ki; Il-Hwa Hong; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Chang-Woo Min; Kyung-Ku Kang; Myeong-Mi Lee; et al. (Molecular and Cellular Biochemistry, 2014)

Transcriptional changes of gibberellin oxidase genes in grapevines with or without gibberellin application during inflorescence development - Chan Jin Jung; Youn Young Hur; Sung-Min Jung; Jung-Ho Noh; Gyung-Ran Do; Seo-June Park; Jong-Chul Nam; Kyo-Sun Park; Hae-Sung Hwang; Doil Choi; Hee Jae Lee (Journal of Plant Research, 2014)

(E)-2,4-Bis(p-hydroxyphenyl)-2-butenal inhibits tumor growth via suppression of NF-κB and induction of death receptor 6 - Jung Ok Ban; Young-Suk Jung; Dae Hwan Kim; Kyung-Ran Park; Hyung-Mun Yun; Nam Jin Lee; Hee Pom Lee; Jeong-Hyun Shim; Heon-Sang Jeong; Yun-Hee Lee; Young Wan Ham; Sang-Bae Han; et al. (Apoptosis, 2014)

Plant-derived mAbs have effective anti-cancer activities by increasing ganglioside expression in colon cancers - Jae-Sung Ryu; Ju-Taek Lee; Malg-Um Lim; Mi-Ran Hwang; Kyung-A Hwang; Young-Ho Cho; Jeong-Hwan Lee; Kisung Ko; Young-Kug Choo (Biotechnology Letters, 2013)

SPARC is involved in the maintenance of mitotically inactivated mouse embryonic fibroblast cells - Jun Yeon Won; Young Jin Lee; Seung-Joon Lee; Woo Jin Kim; Seon-Sook Han; Se-Ran Yang; Heung-Myong Woo; Sung-Min Park; Hyang-Ah Lee; Seok-Ho Hong (In Vitro Cellular & Developmental Biology - Animal, 2013)

Analysis of Substrate Recognition Site 2 (SRS2) in human cytochrome P450 1A2 using whole-plasmid random mutagenesis - Joohwan Kim; Songhee Han; Seunghye Choi; Hyoung-Goo Park; Young-Ran Lim; Hwayoun Lee; Donghak Kim (Molecular & Cellular Toxicology, 2013)

Functional Analysis of Histone Demethylase Jmjd2b on Lipopolysaccharide-Treated Murine Neural Stem Cells (NSCs) - Nando Dulal Das; Mi Ran Choi; Kyoung Hwa Jung; Ji Hyun Park; Hyung Tae Lee; Amitabh Das; Seung Hyun Kim; Young Gyu Chai (Neurotoxicity Research, 2013)

Phylogenetic analysis of porcine astrovirus in domestic pigs and wild boars in South Korea - Meong-Hun Lee; Hye-Young Jeoung; Hye-Ran Park; Ji-Ae Lim; Jae-Young Song; Dong-Jun An (Virus Genes, 2013)

Effects of pargyline on cellular proliferation in human breast cancer cells - Hyung Tae Lee; Kyoung Hwa Jung; Se Kye Kim; Mi Ran Choi; Young Gyu Chai (Molecular & Cellular Toxicology, 2012)

Identification of genes induced by Venturia nashicola in indigenous Korean pear ‘Hwangsilri’ - Il Sheob Shin; Kyung Mi Bae; Ga Young Nam; Byoung-Cheorl Kang; Jaean Chun; Kang Hee Cho; Se Hee Kim; Hyung Seok Choi; Hyun Ran Kim; Hae Sung Hwang; Hee Jae Lee (Horticulture, Environment, and Biotechnology, 2012)

Artificial microRNA-based aldehyde dehydrogenase gene silencing in mice - Hyung Tae Lee; Kyoung Hwa Jung; Mina Baek; Mi Kyung Chung; Mi Ran Choi; Young Gyu Chai (Molecular & Cellular Toxicology, 2012)

Differentially expressed genes in human peripheral blood as potential markers for statin response - Hong-Hee Won; Suk Ran Kim; Oh Young Bang; Sang-Chol Lee; Wooseong Huh; Jae-Wook Ko; Hyung-Gun Kim; Howard L. McLeod; Thomas M. O’Connell; Jong-Won Kim; Soo-Youn Lee (Journal of Molecular Medicine, 2012)

Temporal changes in the abundance of the fish-killing dinoflagellate Karlodinium veneficum (Dinophyceae) in Tongyeong, Korea - Tae-Gyu Park; Yu-Ran Ok; Young-Tae Park; Chang-Kyu Lee (Algae, 2011)

Real-time detection of cellular apoptosis using a rat C6 glioma cell-based assay system - Kyoung Hwa Jung; Young Me Song; Nando Dulal Das; Kyoung Sun Park; Mi Ran Choi; Sang Youn Hwang; Eun Kyu Lee; Moon Kwon Lee; Jaebum Choo; Kyoung Suk Kim; Moo Soung Kim; Sang Rin Lee; et al. (Molecular & Cellular Toxicology, 2011)

Ethanol-induced small heat shock protein genes in the differentiation of mouse embryonic neural stem cells - Mi Ran Choi; Kyoung Hwa Jung; Ji Hyun Park; Nando Dulal Das; Mi Kyung Chung; Ihn Geun Choi; Boung Chul Lee; Kyoung Sun Park; Young Gyu Chai (Archives of Toxicology, 2011)

Molecular characterization of a cysteine proteinase inhibitor, PgCPI, from Panax ginseng C. A. Meyer - Dae-Young Jung; Ok Ran Lee; Yu-Jin Kim; Jung-Hye Lee; Rama Krishna Pulla; Gayathri Sathiyaraj; Ju-Sun Shim; Deok-Chun Yang (Acta Physiologiae Plantarum, 2010)

Bile tolerant Lactobacillus reuteri isolated from pig feces inhibits enteric bacterial pathogens and porcine rotavirus - Byeong Joo Seo; Mi Ran Mun; Rejish Kumar V. J; Chul-Joong Kim; Insun Lee; Young-Hyo Chang; Yong-Ha Park (Veterinary Research Communications, 2010)

Stability of Multi-Permeable Reactive Barriers for Long Term Removal of Mixed Contaminants - Jai-Young Lee; Kui-Jae Lee; Sun Young Youm; Mi-Ran Lee; Seralathan Kamala-Kannan; Byung-Taek Oh (Bulletin of Environmental Contamination and Toxicology, 2010)

ATHB23, an Arabidopsis class I homeodomain-leucine zipper gene, is expressed in the adaxial region of young leaves - Yun-Kyoung Kim; Ora Son; Mi-Ran Kim; Kyoung-Hee Nam; Gyung-Tae Kim; Myeong-Sok Lee; Soon-Young Choi; Choong-Ill Cheon (Plant Cell Reports, 2007)

Engineering the Japanese encephalitis virus RNA genome for the expression of foreign genes of various sizes: Implications for packaging capacity and RNA replication efficiency - Sang-Im Yun; Yu-Jeong Choi; Xiao-Fang Yu; Jae-Young Song; Young-Hak Shin; Young-Ran Ju; Seok-Yong Kim; Young-Min Lee (Journal of NeuroVirology, 2007)

In vitro and in planta Interaction Evidence between Nicotiana tabacum Thaumatin-Like Protein 1 (TLP1) and Cucumber mosaic virus Proteins - Min Jung Kim; Byung-Kook Ham; Hwa Ran Kim; In-Ju Lee; Young Jin Kim; Ki Hyun Ryu; Young In Park; Kyung-Hee Paek (Plant Molecular Biology, 2005)

Expression of tobacco cDNA encoding phytochelatin synthase promotes tolerance to and accumulation of Cd and As inSaccharomyces cerevisiae - Young Jin Kim; Kwang Seok Chang; Mi Ran Lee; Jong Hoon Kim; Chang Eun Lee; Yoon Joo Jeon; Jong Soon Choi; Hyoung Sun Shin; Seongbin Hwang (Journal of Plant Biology, 2005)

The suggestive association of eotaxin-2 and eotaxin-3 gene polymorphisms in Korean population with allergic rhinitis - Soo-Cheon Chae; Young-Ran Park; Gyung-Jae Oh; Jae-Hoon Lee; Hun-Taeg Chung (Immunogenetics, 2005)

Anti-fungal effects of phenolic amides isolated from the root bark of Lycium chinense - Dong Gun Lee; Yoonkyung Park; Mi-Ran Kim; Hyun Jun Jung; Young Bae Seu; Kyung-Soo Hahm; Eun-Rhan Woo (Biotechnology Letters, 2004)

CHRK1, a chitinase-related receptor-like kinase, plays a role in plant development and cytokinin homeostasis in tobacco - Jeong Hee Lee; Kentaro Takei; Hitoshi Sakakibara; Hye Sun Cho; Do Myung Kim; Youn Sung Kim; Sung Ran Min; Woo Taek Kim; Dae Young Sohn; Yong Pyo Lim; Hyun-Sook Pai (Plant Molecular Biology, 2003)